Muscle and tendon adaptation in adolescent athletes: A longitudinal study. (8th December 2015) - Mersmann, F.; Bohm, S.; Schroll, A.; Boeth, H.; Duda, G. N.; Arampatzis, A.
Abstract : There is evidence that a non‐uniform adaptation of muscle and tendon in young athletes results in increased tendon stress during mid‐adolescence. The present longitudinal study investigated the development of the morphological and mechanical properties of muscle and tendon of volleyball athletes in a time period of 2 years from mid‐adolescence to late adolescence. Eighteen elite volleyball athletes participated in magnetic resonance imaging and ultrasound‐dynamometry sessions to determine quadriceps femoris muscle strength, vastus lateralis, medialis and intermedius morphology, and patellar tendon mechanical and morphological properties in mid‐adolescence (16 ± 1 years) and late adolescence (18 ± 1 years). Muscle strength, anatomical cross‐sectional area (CSA), and volume showed significant ( P  < 0.05) but moderate increases of 13%, 6%, and 6%, respectively. The increase of patellar tendon CSA ( P  < 0.05) was substantially greater (27%) and went in line with increased stiffness ( P  < 0.05; 25%) and reduced stress ( P  < 0.05; 9%). During late adolescence, a pronounced hypertrophy of the patellar tendon led to a mechanical strengthening of the tendon in relation to the functional and morphological development of the muscle. These adaptive processes may compensate the unfavorable relation of muscle strength and tendon loading capacity in mid‐adolescence and might have implications on athletic performance and tendon injury risk.